Production of liquid fuels from thermal cracking of palm oil in the presence of natural granite as a thermal cracking agent / Sharifah Noor Munirah Syed Mohamed Yunus - Syed Mohamed Yunus, Sharifah Noor Munirah (2016)
The search for alternatives to petroleum based fuels has led to the development of fuels from various sources, including renewable feedstocks such as vegetable oils. Cracking of vegetable oils is one of the invented processes to improve the yield of liquid fuels. However, the current study more concentrated on the catalytic cracking since the reaction would give high conversion with high yield of liquid fuels product. The use of this method on the industrial scale is limited by the high cost of catalyst. Therefore, to solve this problem, the natural granite was used as a thermal cracking agent since the availability of natural granite in market is more economically compare the used of catalysts. The purpose of this research is to study the potential of natural granite as a thermal cracking agent in thermal cracking for the production of liquid fuels from palm oil with physical and chemical properties similar to gasoline and comparing with ASTM specifications. The natural granite was characterized with X-ray Fluorescence (XRF), Thermogravimetric Analyzer (TGA) and Fourier Transform Infra-Red (FTIR) methods to characterize the physical and chemical properties. The thermal cracking of palm oil was conducted in a batch reactor under atmospheric pressure for a 4 hour reaction time with the effect of thermal cracking with and without natural granite, different size (<1 cm, 2-3 cm and > 3 cm) and loading of natural granite (1,3 and 5 kg). The conversion reached to a maximum value of 60 wt%, 14.4 wt% of total liquid and 6.4 wt% of liquid fuels for olein. The liquid fuels essentially consisted of C5-C18 of hydrocarbons. 3 kg of natural granite considered the best amount with high selectivity of light hydrocarbon. All physical properties of liquid fuels like calorific value, kinematic viscosity, flash point, water content, density, and elemental analysis were comparable with commercial gasoline and can be used as alternative fuels. Analysis of the liquid fuels indicates that thermal cracking of palm oil with natural granite as a thermal cracking agent are promising, cost effectively and more profitable due to energy saving.